Alkylation of microfibrillated cellulose – A green and efficient method for use in fiber-reinforced composites. (22nd September 2017) - Lepetit, Amaury; Drolet, Richard; Tolnai, Balázs; Montplaisir, Daniel; Zerrouki, Rachida
Abstract: Microfibrillated cellulose (MFC) fibers were alkylated by propargyl bromide, allyl bromide and propyl bromide in an aqueous medium without any stirring. The chemical modifications were confirmed by Fourier transform infrared spectroscopy (FTIR), solid-state 13 C nuclear magnetic resonance spectroscopy (NMR) and X-ray photoelectron spectrometry (XPS). The alkylated MFC fibers were obtained with degrees of substitution (DS) ranging from 0.12 to 0.33. All the samples were combined with low-density polyethylene (LDPE), and then the morphology, mechanical properties and water absorption behavior of the ensuing composites were investigated. Study of the morphology of the composites by Scanning Electron Microscopy (SEM) shows a slight improvement of the MFC/LDPE interface after allylation and propargylation. Moreover, the mechanical properties of the composites were significantly improved and the moisture absorption was reduced compared to unmodified MFC fibers. Graphical abstract: Highlights: Alkylation of MFC fibers was performed in aqueous medium. Unmodified and alkylated MFC LDPE-composites were prepared. Mechanical properties of the composites improved after alkylation. Propargylation and allylation led to a decrease of the water absorption behavior of the MFC-composites.